2020
DOI: 10.3390/rs12203312
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Hyperspectral Remote Sensing for Soil Gradation

Abstract: Soil gradation is an important characteristic for soil mechanics. Traditionally soil gradation is performed by sieve analysis using a sample from the field. In this research, we are interested in the application of hyperspectral remote sensing to characterize soil gradation. The specific objective of this work is to explore the application of hyperspectral remote sensing to be used as an alternative to traditional soil gradation estimation. The advantage of such an approach is that it would provide the soil gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
6
Order By: Relevance
“…Известные методы дистанционного спектрального определения структурного состава почвы условно можно разделить на следующие: ̶ Мультиспектральные спутниковые методы видимого и ближнего ИК диапазонов [3]; ̶ Мультиспектральные спутниковые методы ИК диапазона [4]; ̶ Гиперспектральные методы [5]. Как отмечается в работе [3], спектральные данные, полученные от LandsatTM7, с шести спектральных каналов позволяет различить структурный состав незаросшей почвы по таким составляющим как песок, песочный известняк, глинистый известняк, суглинок, глина.…”
Section: краткий обзор известных методов дистанционного определения с...unclassified
See 2 more Smart Citations
“…Известные методы дистанционного спектрального определения структурного состава почвы условно можно разделить на следующие: ̶ Мультиспектральные спутниковые методы видимого и ближнего ИК диапазонов [3]; ̶ Мультиспектральные спутниковые методы ИК диапазона [4]; ̶ Гиперспектральные методы [5]. Как отмечается в работе [3], спектральные данные, полученные от LandsatTM7, с шести спектральных каналов позволяет различить структурный состав незаросшей почвы по таким составляющим как песок, песочный известняк, глинистый известняк, суглинок, глина.…”
Section: краткий обзор известных методов дистанционного определения с...unclassified
“…Особый интерес представляет возможность использования гиперспектральных методов дистанционного зондирования для определения структурного состава почвы. Так, например, согласно [5][6][7], гиперспектральные методы определения структурного состава почвы разрабатывались с использованием соответствующей, аппаратуры, установленной на борту, как спутников, так и БПЛА. Согласно [5], количественная оценка содержания песка в почве может быть дана с использованием спектральных диапазонов 2200-2400нм и 400 1000нм.…”
Section: краткий обзор известных методов дистанционного определения с...unclassified
See 1 more Smart Citation
“…Studies have shown that it can be applied to soil studies such as using remotely sensed color (red, green, blue) images to build a 3D model to predict the bearing strength of beach sand [15]. Archeologists have used remote sensing to locate buried structures using MIVIS (Multispectral Infrared and Visible Imaging Spectrometer) hyperspectral airborne data [16]; hyperspectral sensors have detected soil gradation [17]; Landsat 8 imagery and Geographic Information Systems [18,19] have been used to model wildfire; Airborne Visible/Infrared Imaging Spectrometer-Next Generation (AVIRIS-NG) hyperspectral data have generated lithological and mineral maps [20,21]; and remote sensing has been used for anomaly/target recognition [22]. Work has also been conducted on thermal remote sensing for a variety of applications like detecting buried objects [23] or landmines [24], quantifying moisture content in mine tailings [25], using ENVISAT AASTR datasets [26] to correlate thermal inertia (TI)/Apparent Thermal Inertia (ATI) to land use/land cover mapping and to soil moisture [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…While it's useful to be able to distinguish between different types of ground surfaces, a critical property that is missing from these analyses is the compressive strength of the underlying material, which is crucial to determine if the material will support a given vehicle. Instead of using classification frameworks to predict surface type, regression models can be constructed that predict a range of surface properties that can be used for strength characterization (Selige et al 2006;Ewing et al 2020). Recent studies have attempted to remotely characterize snow properties using hyperspectral and multispectral sensors (Nolin et al 2000;Dozier and Painter 2004;Gusain et al 2004;Shekhar et al 2019;Haq et al 2019;Singh et al 2019).…”
Section: Introductionmentioning
confidence: 99%